2009
DOI: 10.1016/j.jaci.2008.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for acute asthma in 63 US emergency departments

Abstract: Background Little is known about the quality of acute asthma care in the emergency department (ED). Objectives We sought to determine the concordance of ED management of acute asthma with National Institutes of Health asthma guidelines, to identify ED characteristics predictive of higher guideline concordance, and to assess whether guideline concordance was associated with hospital admission. Methods We conducted a retrospective chart review study of acute asthma as part of the National Emergency Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 25 publications
2
56
1
Order By: Relevance
“…This differs from the findings of the previously cited adult EMNet study, 8 as well as 2 of the 4 previous studies of this issue in children. 3,4,9,10 The process measures used in the adult study were the same 5 level A recommendations as in our study; the study revealed that 100% guideline concordance (in 12 level A and B measures) was associated with a 46% lower admission rate.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This differs from the findings of the previously cited adult EMNet study, 8 as well as 2 of the 4 previous studies of this issue in children. 3,4,9,10 The process measures used in the adult study were the same 5 level A recommendations as in our study; the study revealed that 100% guideline concordance (in 12 level A and B measures) was associated with a 46% lower admission rate.…”
Section: Discussioncontrasting
confidence: 99%
“…14 Employing methods similar to those in an EMNet multicenter study of adults with acute asthma, 8 we derived 7 process measures of asthma care quality from the NIH asthma guidelines 2 ( Table 1).…”
Section: Quality Measuresmentioning
confidence: 99%
See 3 more Smart Citations